Автоматизированный поиск коммерческой информации для решения задач организации виртуальных предприятий - Помилуйко, П.А. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
This article describes approaches and architectural solutions are used in the creation of search systems. business information retrieval from unstructured collections and virtual enterprises organization.